KORELASI ANTARA DERAJAT BERATNYA OSTEOARTHRITIS LUTUT DAN CARTILAGE OLIGOMERIC MATRIX PROTEIN SERUM - Andriyasa, Ketut; Raka Putra, Tjokorda (journal of internal medicine, 2014)
Prevalence of knee Osteoarthritis (OA) in the community is quite high. Diagnosis and assessment of severity of knee OA based on X-ray examination is not so sensitive yet. Various attempts have been made to nd markers of cartilage damage. One potential marker is Cartilage Oligomeric Matrix Protein (COMP). Based on animal studies, the more severity damage of joint cartilage, the more COMP is released. Based on this, researchers want to know whether there is a correlation between the severities of knee OA with serum concentration of COMP in human.This study is a cross sectional analytic study, whose performed in Outpatient clinic RSUP Sanglah Denpasar. The diagnosis of knee OA based on ACR criteria and the degree of knee OA severity is determined based on the Kellgren and Lawrance criteria. COMP patients are checked by using ELISA method. The correlation between the severities of knee OA and serum COMP was analyzed by Spearman correlation test. Level of statistical signicance used was p < 0.05. Sixty-six patients who meet the inclusion criteria are examined, male was 28 (42.4%), women was 38 (57.6%). The mean age is 63.9 ± 7.0 years. The severity of knee OA are: 4.5% for grade one, 35.8% grade two, 38.8% grade three and 20.9% at grade 4. The mean serum COMP concentration is 1084.0 ng/ml. There is a trend of increasingly grade of severity of knee OA, the higher the concentration of serum COMP, but not statistically signicant (r = 0.127, p = 0.31). In conclusion, there is no positif correlation that statistically signicant between severity of knee OA and serum COMP concentration.
Keywords: Osteoarthritis, knee, COMP